Exploring the genetic basis of Newcastle disease virus in chickens: a comprehensive review - Berihulay, Haile; Luo, Wei; Lao, Ainong; Ji, Jian; Cai, Manshan; Shu, Dingming; Luo, Chenglong (Frontiers in Immunology, 2025)
Newcastle disease (ND) is one of the most serious viral diseases affecting chickens and is caused by Newcastle disease virus (NDV), an avian paramyxovirus serotype-1. The virus contains five structural proteins and two nonstructural proteins that interact with the host proteins involved in viral infection and host antiviral responses. Currently, several NDV strains have been molecularly characterized; however, a comprehensive overview of NDV in chickens that addresses recent findings is lacking. This review summarizes the current report of the molecular structure of NDV, including candidate genes and genomic regions, virulence and route of infection, mechanisms of resistance, host immune response, disease resistance mechanisms and effects of NDV on chicken immune performance. Therefore, this review can be used by researchers seeking a comprehensive understanding that can be applied in future breeding programs aimed at enhancing disease resistance.